2013 Boston Marathon - Williams, Heather, 1974- (Sports unite us., 2019)
Presents information on marathons, and specifically discusses the 2013 Boston Marathon at which two bombs exploded, killing three and wounding hundreds. Explores the reaction of the world after the bombing and the way Boston came together to honor the victims.